Data Quality in the Outpatient Setting: Impact on Clinical Decision Support Systems - Berner, Eta S. (American Medical Informatics Association, 2005)
Clinical decision support system (CDSS) performance may vary with the quality of the input data. We assessed the impact of medical record completeness and accuracy on a CDSS that provides risk assessment for gastrointestinal bleeding and recommends therapy when prescribing NSAIDs. We examined the documentation of six data elements in the medical record and the impact on the performance of the CDSS. We reviewed 178 transcribed clinical encounters from standardized patients with predefined clinical histories. Results showed that the mean completeness score across all encounters was .34. The mean correctness score for those elements present was .94. When the available data was input into the CDSS, the missing data elements resulted in inappropriate and unsafe recommendations in almost 77% of the encounters. The results show that important gaps in the medical record can affect the accuracy of a CDSS designed to improve safe prescribing.